Multiple myeloma with extensive AL amyloidosis presenting as chronic diarrhoea. Issue 1 (8th January 2020) - Kogler, William; Canha, Catarina; Makary, Raafat; Omman, Reeba; Isache, Carmen Liliana
Abstract : We present a 52-year-old man admitted to the hospital with diarrhoea and lower extremity weakness ongoing for the past 3 months. The patient was found to have malabsorptive diarrhoea, hypoproliferative anaemia and renal insufficiency with proteinuria. Extensive workup was performed including a bone marrow biopsy with 20% plasma cells, renal and duodenal biopsies with Congo-red staining revealed amyloid deposition. The patient was diagnosed with multiple myeloma and amyloidosis with gastrointestinal, kidney and nerve involvement explaining his presentation with diarrhoea, renal insufficiency and weakness. Throughout his admission, there were incidental findings of asymptomatic hypoglycaemia (serum blood glucose <40 mg/dL), which was later found to be caused by anti-insulin monoclonal antibodies produced by the neoplastic plasma cells. This is an extremely rare manifestation of multiple myeloma with only a few cases reported in the literature.